Natural gas-diesel reactivity controlled compression ignition with negative valve overlap and in-cylinder fuel reforming - Mikulski, Maciej; Balakrishnan, Praveen Ramanujam; Hunicz, Jacek (Elsevier, 2019)
Dual-fuel reactivity controlled compression ignition combustion offers potentially superior overall efficiency and ultra-low nitrogen oxides and soot emissions. Using natural gas as the low reactivity fuel also provides high knock-resistance and carbon dioxide emission reduction. However, the concept suffers from relatively low combustion efficiency at low engine loads, causing unacceptable methane slip. This study tackles this issue, applying numerical simulations to investigate the application of negative valve overlap to improve combustion efficiency of reactivity controlled compression ignition at low engine loads. The objective is modification of in-cylinder thermal and chemical state before combustion, by varying timing and amount of fuel injected directly into the recompressed hot exhaust gases. The study uses TNO's multi-zone, chemical kinetics-based combustion model with variable valve actuation functionality. The simulation is based on two experimentally validated cases: an uncooled exhaust gas recirculation strategy and a lean burn concept. In both cases, negative valve overlap elevates in-cylinder temperature and cuts methane emissions by 15%, without combustion optimization. Crucially, it enables peak exhaust recompression temperatures above 850 K, sufficient for diesel reforming/oxidation. The lean RCCI strategy takes greater advantage of fuel reforming than the exhaust gas recirculation case. Optimum conditions give almost 99% combustion efficiency and ultra-low methane emissions. Net indicated efficiency is 40.5% (@15% load), despite negative valve overlap’s substantial pumping losses. Low-load net efficiency is 5.5 percentage points above the lean strategy baseline and 3 pp. better than the exhaust gas recirculation baseline. This strategy is considered applicable on state-of-the-art dual-fuel gas engines without hardware changes.
Keywords: RCCI; Natural Gas; Variable Valve Actuation; Negative Valve Overlap; Fuel Reforming; Residuals; fi=Energiatekniikka|en=Energy Technology|